Early Maize in the Maya Area. Issue 4 (December 2022) - Lohse, Jon C.; Morgan, Molly; Jones, John G.; Brenner, Mark; Curtis, Jason; Hamilton, W. Derek; Cardona, Karla
Abstract : The history of maize in Central America and surrounding areas has implications for the slow transition from hunting and gathering to agriculture. The spread of early forms of domesticated maize from southern Mexico across Mesoamerica and into South America has been dated to about 8, 700–6, 500 years ago on the basis of a handful of studies relying primarily on the analysis of pollen, phytoliths, or starch grains. Recent genomic data from southern Belize have been used to identify Archaic period south-to-north population movements from lower Central America, suggesting this migration pattern as a mechanism that introduced genetically improved maize races from South America. Gradually, maize productivity increased to the point that it was suitable for use as a staple crop. Here we present a summary of paleoecological data that support the late and uneven entry of maize into the Maya area relative to other regions of Central America and identify the Pacific coastal margin as the probable route by which maize spread southward into Panama and South America. We consider some implications of the early appearance of maize for Late Archaic populations in these areas; for example, with respect to the establishment of sedentary village life.